Pengaruh Green Human Resource Management dan Green Transformational Leadership Terhadap Employee Green Behavior - Wijayanti, Rosalina; Azzuhri, Misbahuddin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The objective of this research is to assess and explain the effects of (1) Green Recruitment and Selections on Employee Green Behavior, (2) Green Training and Development on Employee Green Behavior, (3) Employee Green Involvement on Employee Green Behavior, and (4) Green Transformational Leadership on Employee Green Behavior in the context of Grand Ranggonang Sekayu hotel. Using saturated sampling, 51 employees of the hotel were selected as the respondents of this quantitative explanatory study. The results of the multiple linear regression suggest that (1) Green Recruitment and Selections positively an insignificantly influences Employee Green Behavior, (2) Green Training and Development negatively and insignificantly affects Employee Green Behavior, (3) Employee Green Involvement positively and significantly impacts Employee Green Behavior, and (4) Green Transformational Leadership positively and insignificantly affects Employee Green Behavior. Abstrak Penelitian ini bertujuan untuk menguji dan menjelaskan: 1) Pengaruh Green Recruitment and Selections terhadap Employee Green Behavior; 2) Pengaruh Green Training and Development terhadap Employee Green Behavior; 3) Pengaruh Employee Green Involvement terhadap Employee Green Behavior; 4) Pengaruh Green Transformational Leadership terhadap Employee Green Behavior. Jenis penelitian yang digunakan yaitu explanatory research dengan metode kuantitatif. Penelitian ini menggunakan analisis regresi linear dan hasil dari penelitian ini yaitu: 1) Green Recruitment and Selections memiliki hubungan yang positif tidak signifikan terhadap Employee Green Behavior; 2) Green Training and Development memiliki hubungan yang negatif tidak signifikan terhadap Employee Green Behavior; 3) Employee Green Involvement memiliki hubungan yang positif signifikan terhadap Employee Green Behavior; 4) Green Transformational Leadership memiliki hubungan yang positif tidak signifikan terhadap Employee Green Behavior.